Utilization of Bottom Ash from Biomass Combustion in a Thermal Power Plant to Remove Cadmium from the Aqueous Matrix - Eva Pertile; Tomáš Dvorský; Vojtěch Václavík; Bohdana Šimáčková; Lukáš Balcařík (Molecules)
This study provides a cost-effective method for using bottom ash from biomass combustion, which would otherwise constitute waste, to remove cadmium from acidic industrial wastewater. The X-ray powder diffraction method was used to identify the crystal forms, i.e., the arrangement of atoms in the crystal lattice, and to determine the composition of bottom ash, and the X-ray fluorescence method was used to obtain information on the elemental composition of bottom ash. The Fourier Transform Infrared method was used to analyse and identify the different functional groups occurring in bottom ash. Scanning Electron Microscopy with energy-dispersive X-ray was used to obtain detailed information on the bottom ash surface. The effect of various factors on Cd removal was studied, and optimal experimental conditions were found. The kinetic and thermodynamic equations showed that the removal of Cd2+ using bottom ash from biomass combustion was a single-layer chemical adsorption meeting the requirements of pseudo-second-order kinetics. The limiting parameter for the effective adsorption of Cd2+ using bottom ash from biomass combustion is its alkaline nature. It can only be used for solutions with pH < 2, which, on the other hand, is its advantage in practical application, namely, in the final treatment of acidic industrial wastewater.